2023
DOI: 10.3390/jpm13050776
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Purine-Metabolism-Related Gene Signature for Predicting Ovarian Cancer Prognosis, Immune Landscape, and Potential Treatment Options

Abstract: Purine metabolism is an important branch of metabolic reprogramming and has received increasing attention in cancer research. Ovarian cancer is an extremely dangerous gynecologic malignancy for which there are no adequate tools to predict prognostic risk. Here, we identified a prognostic signature consisting of nine genes related to purine metabolism, including ACSM1, CACNA1C, EPHA4, TPM3, PDIA4, JUNB, EXOSC4, TRPM2, and CXCL9. The risk groups defined by the signature are able to distinguish the prognostic ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…Our data also showed a decrease in glutamine, which is one of the substrates that contribute to the de novo biosynthetic pathway of purine metabolism [29], which may indicate a reliance on increased glutamine consumption to support these changes in nucleotide metabolism. Notably, several other studies have shown that purine metabolism is a metabolic vulnerability of cancer cells and that this pathway is implicated in therapy resistance in a number of cancer types [37][38][39][40][41][42][43][44][45]. The current study shows that purine metabolism is a differentiator for resistant cancer cells in an entire drug class, and that changes in certain aspects of this pathway (e.g., increases in xanthine-and hypoxanthine-related reactions) are the most robust differentiators.…”
Section: Discussionsupporting
confidence: 60%
“…Our data also showed a decrease in glutamine, which is one of the substrates that contribute to the de novo biosynthetic pathway of purine metabolism [29], which may indicate a reliance on increased glutamine consumption to support these changes in nucleotide metabolism. Notably, several other studies have shown that purine metabolism is a metabolic vulnerability of cancer cells and that this pathway is implicated in therapy resistance in a number of cancer types [37][38][39][40][41][42][43][44][45]. The current study shows that purine metabolism is a differentiator for resistant cancer cells in an entire drug class, and that changes in certain aspects of this pathway (e.g., increases in xanthine-and hypoxanthine-related reactions) are the most robust differentiators.…”
Section: Discussionsupporting
confidence: 60%
“…Increasing evidence suggests that multigene-based gene signatures are promising prognosis prediction models for OC [3][4][5][6][7][8][9][10]. However, despite having had several multigene signatures established for OC, their prognostic accuracy remains weak.…”
Section: Introductionmentioning
confidence: 99%